b - d (b, 2001)
History of the land revenue system of Bangladesh from ancient times to 1763.
Includes bibliographical references (v. 1, p. 416-453).
In Bengali; includes passages in English.
Keywords: Land tenure -- Bangladesh -- History; Land tenure